KAJIAN MORFOLOGI Drosera burmanni Vahl. DARI DESA MAHOLO, KECAMATAN LORE TIMUR, KABUPATEN POSO, SULAWESI TENGAH - Rusmin Rusmin; Ramadanil Pitopang (Biocelebes, 2020)
The research entitled Morphological Studies of Drosera burmanni Vahl. From Maholo Village, Lore Timur District, Poso Regency Cental Sulawesi has been conducted from March to April 2017. The objective of research was to described the morphology character of Drosera which was found in studied area. The research was used botanical exploration in the studied area the morphological character was described followed Van Steenis (1953). The result showed the there were 820 individuals of Drosera burmanni Vahl. the description is provided in this paper.